Eficácia da acupuntura como tratamento adjuvante da cefaleia crônica - MAYRINK, Wildete Carvalho (2016)
Introdution: More than 90 % of the population had or will have at least one headache crisis in life and 3 % have them regularly. It is considered a public health issue.The effectiveness of acupuncture in chronic headache is still a reason of controversies. Objectives: Evaluate the effectiveness of acupuncture as an adjuvant analgesic treatment for chronic headache and the influence of this treatment on quality of life. Methods: There were selected 34 patients by chronic pain service of a teaching hospital, divided in two groups: True acupuncture (group I), where were used the recommended points for the Traditional Chinese Medicine paragraph for each type of headache; and sham acupuncture (group II), where the needles were inserted into a device (moxa on button), used the same points in Group I. Both groups used the prescribed preventive medication to pain. The assessment methods were: Scale Verbal numerical before (ENV1) and after (ENV2) to treatment; the number of attacks and number of analgesics used during the first and second months of treatment. Quality of life was also assessed before and after the treatment through the Brazilian version of the Quality of Life Questionnaire (QOL) SF-6D 2002. Results: The true acupuncture group showed greater effectiveness in controlling pain in chronic headache, statistically significant in all items compared with the sham acupuncture group, including improvement in quality of life. Conclusions Acupuncture can be considered an adjuvant treatment of chronic headache, reducing the intensity of pain, the number of attacks, quantity of analgesics, as well as improve the patients’s quality of life.